La pluma-bisturí. Literatura y escritura en Michel Foucault - Gordillo López, Jorge Andrés (2025)
I am interested in trying to formulate the question about the particularities of literature and its link with writing today, through the contributions that Michel Foucault made between 1963 and 1971, compiled in the book The Great Foreigner. To think about literature. Specifically, I will focus on Foucauldian affirmation of certain literature understood as a negative figure, as well as on the specificities of its wake.